ARCHIVING MANAGEMENT SYSTEM AT THE REPRESENTATIVE OFFICE OF THE NATIONAL POPULATION AND FAMILY PLANNING AGENCY (BKKBN) OF SOUTH SULAWESI PROVINCE - Indawati, Indawati; Guntur, Muhammad; Darwis, Muh (Universitas Negeri Makassar, 2025)
This study aims to determine the Archive Management System at the Representative Office of the National Family Planning Population Agency (BKKBN) of South Sulawesi Province. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The data that has been obtained from the research results are processed using qualitative analysis with data collection techniques, namely observation, interviews, and documentation. The data obtained from the results of the study were processed using data analysis techniques, data reduction, data presentation and conclusion. The results of the study show that the Archives Management System at the Representative Office of the National Family Planning Population Agency (BKKBN) of South Sulawesi Province is seen from Ahmad Saransi's Archive Management (2014), namely: (1) Creation of Archives, (2) Arrangement/Storage of Archives, (3) Borrowing Archives, (4) Rediscovery of Archives, (5) Maintenance of Archives, (6) Shrinkage of Archives shows optimal results. The assessment of the Archives Management System is seen from the observations of researchers and the results of interviews between researchers and informants, so it can be concluded that this archive management can be said to be going well. This is proven by the existence of human resources who are experts in managing archives consisting of young archivists, first-time archivists and skilled archivists and are supported by adequate facilities and infrastructure so that the archive management becomes optimal.